PHOTOMETRIC SOLUTIONS AND SPOT MODEL OF THE CONTACT BINARY AB ANDROMEDAE - Jae Woo Lee; Chun-Hwey Kim; Wonyong Han; Ho Jin; Kyu-Dong Oh (Journal of Astronomy and Space Sciences, 2003)
We performed CCD photometric observations of the W-type contact binary AB And for 10 nights from November 1995 to December 1999 using the 61-cm reflector and BVR filters at Sobaeksan Optical Astronomy Observatory. From our observations, the seasonal light curves of AB And for 1995, 1996 and 1999 were completed and 8 new times of minimum light were determined. Newly obtained light curves show that strong light variations occurred in AB And during the past five years. We adopted the 1996 light curves as reference ones and obtained the photometric solutions of them with contact mode in the Wilson-Devinney binary code. Assuming such light variations were produced by the existence of a star spot (or star spots) in the analysis, we derived the system parameters and analyzed the 1995 and 1999 light curves by adjusting only the spot parameters. As the results, we interpreted that those light variations are produced by the simultaneous existence of a hot spot and a cool spot on the secondary. We could infer that the hot spot on the secondary is produced due to mass exchange between the components suggested by Lee (1999).